Al-Farabi and Ibn Sina on the Relationship between Philosophy and Jurisprudence in the Classification of Sciences - Tahereh Kamalizadeh (حکمت سینوی)
The classification of sciences is a fundamental topic in epistemology and has a significant impact on determining the position, role, and function of each branch of knowledge. Considering the centrality of wisdom (ḥikmah) and Islamic law (shariʿah) in Islamic thought, the classification of sciences has sometimes been structured around these two principles. This paper investigates the relationship between philosophy and jurisprudence, or ḥikmah and shariʿah, as articulated in the classification systems of Al-Farabi and Ibn Sina. It examines the foundations, implications, and consequences of their approaches within their respective philosophical frameworks. The research employs a descriptive-analytical methodology. The findings reveal that both philosophers acknowledge the compatibility of philosophy and religion, but their prioritizations differ. Al-Farabi prioritizes philosophy, placing jurisprudence and theology under practical wisdom, which is subordinate to theoretical wisdom. In contrast, Ibn Sina prioritizes religion, considering shariʿah as an independent science within practical wisdom, distinct from human sciences and with a divine origin. Ibn Sina views shariʿah as an independent science alongside political science, not as a branch of it. By granting shariʿah an independent identity, Ibn Sina lends it credibility and creates conditions for its potential substitution for practical wisdom in the trajectory of Islamic philosophy. He lays the groundwork for the two sciences of usul al-din (theology) and furuʿ al-din (jurisprudence). It appears that Ibn Sina perceives the realization of philosophy in the Islamic society of his time in the Islamization of philosophy and the validation of religious sciences. Therefore, compared to Al-Farabi, Ibn Sina is more concerned with the Islamization of philosophy and seeks to harmonize the philosophy of his predecessors with his own society.